PEREKAYASAAN FEMINIMITAS TOKOH UTAMA DALAM NOVEL FEMALE UNDER COVER! KARYA NORAH VINCENT - Anggreini, Icha Syari; Rumadi, Hadi; ', Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack : The engineering femininity arises because of several reasons, one of the novels that lifted the story of the novel female perekayasan under cover! Norah Vincent's work. The problem that arises is "How Feminine Technique Main Figures in the Novel Female Undercover! Norah Vincent Works". The purpose of this document on the main character engineering describes female feminine female cover! Norah Vincent's work. The benefits of this research are divided into three theoretical, practical and educational. First Operational Definitions, Engineering feminimtas is a process or a way to manipulate someone who manipulates others by changing the appearance, how to talk, how even the attitude of women walks to become men in society and trying to make up for what He is not known by others. Secondly, the main character in the novel is the one who has always been told in a novel or person who has always been the centerpiece of the conversation. The data source of this research is the new female under cover !. These research data are evidence of feminine technique in the field of language, gesture, and supporting accessory performances by the main character of the novel. The collection of data used technique documentation techniques. Mechanical analysis using qualitative descriptive technique. Validity of data using triangulation techniques using two validators who are experts in their field. The results of the study are a form of femininity technique, which is divided into 27 105 in emotional, physical, 24 and 54 data in terms of masculinity by the leading role that obtained data processing system data.Keywords: Engineering femininity, the main character, the new woman under cover !.